Thiamine Level in Out-of-hospital Cardiac Arrest Patients - Buranasakda, Marturod; Pattanarattanamolee, Ratrawee (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Thiamine deficiency is more common in critically ill patients. Administration of thiamine in cardiac arrest mice has improved survival and neurological outcomes. Evidence for thiamine deficiency in cardiac arrest humans is insufficient to support routine use of thiamine in cardiac arrest patients. AIM: This study aimed to determine thiamine blood levels in cardiac arrest patients to understand whether the presence of thiamine deficiency is common in cardiac arrest patients. METHODS: A prospective descriptive study from April 2017 to March 2018, on 24 adult out-of-hospital cardiac arrest patients. We used the high-performance liquid chromatography technique to determine whole blood thiamine pyrophosphate levels in cardiac arrest patients who arrived at the emergency department within 1 h of the onset of a cardiac arrest. RESULTS: The mean thiamine pyrophosphate level within 1 h of the onset of a cardiac arrest was 170.9 ± 56.7 nmol/L. Only one participant had thiamine deficiency according to the cut-off level for thiamine pyrophosphate in whole blood of <70 nmol/L. Fourteen patients had spontaneous return of circulation. Thiamine pyrophosphate levels were not different between the two groups of patients who had and did not have the return of spontaneous circulation at the emergency department. CONCLUSION: Little evidence was found to support thiamine deficiency as a feature among our cardiac arrest patients. A study with a larger population is required for more meaningful statistical analysis. As there is no consensus on cut-off level for thiamine deficiency diagnosis, the level of thiamine pyrophosphate in specific populations should be evaluated to establish reference values.